Electricity energy produced by short-term hydrothermal Coordination - yongchaiyudh, Nuttapott; Prapai, Sompotsh (Engineering and Applied Science Research, 2015)
The co-operation, between hydro and thermal powered systems, during the short period to produce electricity to cope with consumer’s demand during peak period is considered to be the most suitable and economical. The co-operation and distribution of the above mentioned (hydro-thermal) systems, during the peak demand, are based on data complied from Electricity Generating Authority of Thailand. The experiment can be done by arrange the two generating systems to station on the same site, for the purpose of coordinating to two systems to each other, to get result of the power plant characteristic constant will be used to generate the electricity during the peak period.